Subclinical cardiovascular disease in HIV controller and long‐term nonprogressor populations. Issue 4 (14th November 2019) - Brusca, RM; Hanna, DB; Wada, NI; Blankson, JN; Witt, MD; Jacobson, LP; Kingsley, L; Palella, FJ; Budoff, M; Brown, TT; Anastos, K; Lazar, JM; et al.
Abstract : Objectives: Elite controllers (ECs), viraemic controllers (VCs), and long‐term nonprogressors (LTNPs) control HIV viral replication or maintain CD4 T‐cell counts without antiretroviral therapy, but may have increased cardiovascular disease (CVD) risk compared to HIV‐uninfected persons. We evaluated subclinical carotid and coronary atherosclerosis and inflammatory biomarker levels among HIV controllers, LTNPs and noncontrollers and HIV‐uninfected individuals in the Multicenter AIDS Cohort Study (MACS) and the Women's Interagency HIV Study (WIHS). Methods: We measured carotid plaque presence and common carotid artery intima‐media thickness (IMT) in 1729 women and 1308 men, and the presence of coronary artery calcium and plaque in a subgroup of men. Associations between HIV control category and carotid and coronary plaque prevalences were assessed by multivariable regression analyses adjusting for demographics and CVD risk factors. Serum inflammatory biomarker concentrations [soluble CD163 (sCD163), soluble CD14 (sCD14), galectin‐3 (Gal‐3), galectin‐3 binding protein (Gal‐3BP) and interleukin (IL)‐6] were measured and associations with HIV control category assessed. Results: We included 135 HIV controllers (30 ECs) and 135 LTNPs in the study. Carotid plaque prevalence and carotid IMT were similar in HIV controllers, LTNPs and HIV‐uninfected individuals. HIV controllers and LTNPs had lower prevalences of carotid plaque compared to viraemic HIV‐infected individuals. The prevalence of coronary atherosclerosis was similar in HIV controllers/LTNPs compared to HIV‐uninfected and viraemic HIV‐infected men. Controllers and LTNPs had higher concentrations of sCD163 and sCD14 compared to HIV‐uninfected persons. Conclusions: Subclinical CVD was similar in HIV controllers, LTNPs and HIV‐uninfected individuals despite elevated levels of some inflammatory biomarkers. Future studies of HIV controllers and LTNPs are needed to characterize the risk of CVD among HIV‐infected persons.